Revolutionary War on Wednesday - Osborne, Mary Pope.; Murdocca, Sal (New York : Random House, 2000)
Using their magic tree house, Jack and Annie travel back to the time of the American Revolution and help General George Washington during his famous crossing of the Delaware River.
"A Stepping Stone book.".
3.8
3-6
Keywords: Washington, George, -- 1732-1799 -- Juvenile fiction; Washington, George, -- 1732-1799 -- Fiction; Washington, George, -- 1732-1799 -- Fiction; Annie (Fictitious character : Osborne) -- Juvenile fiction; Jack (Fictitious character : Osborne) -- Juvenile fiction; Magic -- Juvenile fiction; Time travel -- Juvenile fiction; Tree houses -- Juvenile fiction; Annie (Fictitious character : Osborne) -- Fiction; Jack (Fictitious character : Osborne) -- Fiction; Magic -- Fiction; Time travel -- Fiction; Tree houses -- Fiction; Annie (Fictional character : Osborne) -- Fiction; Jack (Fictional character : Osborne) -- Fiction; Magic -- Fiction; Time travel -- Fiction; Tree houses -- Fiction; United States -- History -- 1775-1783, Revolution -- Fiction; United States -- History -- Revolution, 1775-1783 -- Juvenile fiction; United States -- History -- Revolution, 1775-1783 -- Fiction